2022
DOI: 10.3892/ijo.2022.5441
|View full text |Cite
|
Sign up to set email alerts
|

uPAR, beyond regulating physiological functions, has orchestrated roles in cancer (Review)

Abstract: Urokinase-type plasminogen activator receptor (uPAR) serves as the receptor for uPA and the uPA-uPAR complex initiates the extracellular matrix degradation cascade. In cancer, aberrantly elevated uPAR expression is associated with invasion and metastasis, as well as cancer proliferation and survival, thereby rendering uPAR an effective marker for prognosis and a target for therapy. Although uPAR is transiently expressed at limited amounts in normal tissues and certain non-cancer pathological processes, their u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 131 publications
0
6
0
Order By: Relevance
“…[ 42 ] UPAR interacts with different transmembrane proteins to activate intracellular signals mediated by mitogen‐activated protein kinase and further promotes the initiation and progression of many types of human cancer. [ 58 ] Moreover, high levels of UPAR in peripheral blood and tumor tissue are closely associated with the poor prognosis of patients. [ 59 ] MASP2, as a member of the serine proteases family, is a key regulator in the complement‐activated lectin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…[ 42 ] UPAR interacts with different transmembrane proteins to activate intracellular signals mediated by mitogen‐activated protein kinase and further promotes the initiation and progression of many types of human cancer. [ 58 ] Moreover, high levels of UPAR in peripheral blood and tumor tissue are closely associated with the poor prognosis of patients. [ 59 ] MASP2, as a member of the serine proteases family, is a key regulator in the complement‐activated lectin pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The urokinase plasminogen activator surface receptor (uPAR), also known as CD87, serves as a receptor for urokinase plasminogen activator (uPA), a serine protease implicated in tissue remodeling, cell migration, and embryogenesis during physiological processes [47]. uPAR plays diverse roles in various pathological processes in cancer due to its proteolytic and non-proteolytic functions.…”
Section: Uparmentioning
confidence: 99%
“…Urokinase plasminogen activator (uPAR, CD87), a typical GPI‐anchored protein, can regulate plasminogen activation, and cell migration, adhesion, and proliferation. Circulating uPAR in cancer patients has been demonstrated to be associated with tumor malignancy, thereby representing a valuable prognostic marker in certain types of cancer (Wang et al, 2022). It is found that recombinant GPLD1 expression in ovarian cancer can stimulate uPAR release up to fourfolds.…”
Section: Roles Of Gpld1 In Chronic Diseasesmentioning
confidence: 99%